IMPLEMENTATION OF DIVERSION TOWARDS CHILDREN IN CONFENCE WITH THE LAW AT THE INVESTIGATION LEVEL AT THE YAPEN ISLANDS POLICE - Fitriyah Ingratubun (Faculty of Law, Universitas Pekalongan, 2020)
This study seeks to ascertain the implementation of diversion by investigator as a means of resolving criminal cases at the Yapen Islands Police, as well as the efforts and obstacles in implementing diversion for children in conflict with the law at the investigation level at the Yapen Islands Police. This is normative study in which the application of regulations or norms in positive law is examined. Aside from that, academics employ empirical juridical research methodologies, which involve examining events or happenings inside society, which is a social phenomenon related to law. The research findings indicate that the implementation of diversion against minors who are in violation of the law at the investigative level at the police station Yapen Islands in compliance with Law Number 11 of 2012 on the Juvenile Criminal Justice System. Diversion was accomplished by involving linked parties, both victims and children perpetrators of a criminal conduct. However, the processing of criminal crimes committed not all children attempt diversion. This is because juvenile perpetrators who do criminal crimes are performed by people who are the same, so investigators do not need to perform diversion. The presence of institutions with internal authority that provide guidance to children, such as a Development Institute Special Children (LPKA), Temporary Child Placement Institution (LPAS), and The Social Welfare Implementation Institution (LPKS), is expected to reduce the number of crimes committed by children, so that children who are in conflict with the law do not repeat the same act breaking the law. Repetition of criminal activities performed by children who are in dispute with the law demonstrates that the goal of diversion has not been met, and hence diversion measures against minors may not be necessary.